Skin histology and its role in heat dissipation in three pinniped species - Khamas Wael A; Smodlaka Hrvoje; Leach-Robinson Jessica; Palmer Lauren (Acta Veterinaria Scandinavica, 2012)
Abstract Background Pinnipeds have a thick blubber layer and may have difficulty maintaining their body temperature during hot weather when on land. The skin is the main thermoregulatory conduit which emits excessive body heat. Methods Thorough evaluation of the skin histology in three pinniped species; the California sea lion- Zalophus californianus , the Pacific harbor seal- Phoca vitulina richardsi , and the Northern elephant seal- Mirounga angustirostris , was conducted to identify the presence, location and distribution of skin structures which contribute to thermoregulation. These structures included hair, adipose tissue, sweat glands, vasculature, and arteriovenous anastomoses (AVA). Thermal imaging was performed on live animals of the same species to correlate histological findings with thermal emission of the skin. Results The presence and distribution of skin structures directly relates to emissivity of the skin in all three species. Emissivity of skin in phocids (Pacific harbor and Northern elephant seal s ) follows a different pattern than skin in otariids (California sea lions). The flipper skin in phocids tends to be the most emissive region during hot weather and least emissive during cold weather. On the contrary in otariids, skin of the entire body has a tendency to be emissive during both hot and cold weather. Conclusion Heat dissipation of the skin directly relates to the presence and distribution of skin structures in all three species. Different skin thermal dissipation patterns were observed in phocid versus otariid seals. Observed thermal patterns can be used for proper understanding of optimum thermal needs of seals housed in research facilities, rescue centers and zoo exhibits.